ISOLATION AND IDENTIFICATION MOMORDICIN I FROM LEAVES EXTRACT OF Momordica charantia L. - N. M. Purnawati (Jurnal Kimia (Journal of Chemistry), 2008)
Momordicin I has been isolated from dichloromethane extract of leaves Momordica charantia, L. Theisolation was done by fractionation the dichloromethane extract followed by bioassay using artemia salina,L larvae.The crude extract was fractionated through reverse phase column chromatography (C18 Sep-Pak) with eluotropicseries solution of MeOH: H2O (0-100% MeOH). The most active fraction, F9 (80% MeOH-20% H2O) was purifiedby recrystallisation from chloroform to yield a white crystal melted at 125-128oC. The structure of the activecompound was determined by interpretation of the spectral data (IR, 1HNMR, 13CNMR, DEPT, HCOSY, HMCOSY,HMBC and MS) and its structure was elucidated as 3,7,23-trihydroxycucurbitan-5,24-dien-19-al which is known asmomordicin I.